(untitled) (Global Journals of Research in Engineering, 2012)
The use of autonomous vehicles for a wide variety of applications has been increasing during the latest years Land-based vehicles can be used for many purposes but are not as versatile as could be desired because they are dependent on the terrain Aerial vehicles such as aero planes and helicopters do not depend on the terrain in the area of operation as the land based vehicle An autonomous helicopter has an advantage in maneuverability compared to an autonomous aero plane which is not able to hover stand still in the air This and the ability to take off and land in limited spaces are clear advantages of the autonomous helicopter An autonomous helicopter is a versatile platform for a wide variety of applications It can be used in situations as agricultural crop dusting search and rescue missions inspection of bridges or power lines surveillance of larger areas etc Helicopters are complex high performance machines designed to ensure the safety of their occupants during their expected lifetimes To accomplish their goals helicopters require extensive maintenance during their lifetimes at set intervals whether necessary or not To help alleviate the need for unnecessary maintenance condition based maintenance systems are under heavy development with the military expressing much interest in such systems As the name implies condition-based maintenance systems rely on information about the condition of various mechanical components to determine when maintenance is necessary This has the potential to greatly reduce cost and enhance safety The system developed here uses data from three sensors to monitor the condition of a radio-controlled helicopter Data from the sensors is transmitted to a microcontroller where it is processed before being transferred to actuators and eventually to a computer for storage and visualization The system must fulfill several requirements imposed by the constraints of the radio-controlled helicopter mainly small